UJI ANTIBAKTERI SEDIAAN OBAT KUMUR EKSTRAK DAUN PANDAN WANGI (Pandanus amaryllifolius Roxb) TERHADAP Streptococcus mutans - Oom Komala; Putri; Dwi Indriati (Universitas Pakuan, 2017)
Pandanus amaryllifolius Roxb leaf has potential as an antibacterial. The research aims to know the ability of stocks to mouthwash scented pandan leaf extract inhibits Streptococcus mutans and in determining the fragrant pandanus phytochemicals compounds. Wide-Area Drag testing (LDH) mouthwash extracts was performed with a concentration of 15%, 17.5% and 20%. Test the phytochemical saponins, alkaloids, tannins and flavonoids qualitatively on 0.5 g powder. Testing stabilita include organoleptik observations of color, aroma, taste preparation, test the pH, specific gravity and viscosity. The results showed that the material of pandanus leaf extract mouthwash scented antibacterial nature against Streptococcus mutans with a concentration of extracts of 15%, 17.5% and 20% showed values of LDH consecutive 16.3 mm; 22.6 mm and 28.3 mm earlier in the week while in week 8 loss to the value of LDH is 12.5 mm; 15.5 mm; and 19.6 mm. The active compounds in the leaves of pandanus is alkaloids, saponins, tannins and flavonoids. Mouthwashes stored at 25-30 C for 8 weeks are relatively stable for color, flavor, taste, pH, specific gravity, and viscosity, compared to a temperature of 40oC.Key words: Pandan fragrance, Streptococcus mutans, mouthwash